Biliary reflux after laparoscopic modified antireflux monoanastomotic gastric bypass surgery - M. V. Nikolaiev (Patologìâ)
Aim. Determination of biliary reflux in patients with morbid obesity after a single-anastomotic gastric bypass operation performed in the clinic's modification and according to the classical Roux-en-Y gastric bypass technique. Development of diagnostic criteria for biliary reflux